(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Aims: The study aims at assess nurses knowledge towards Pneumothorax and determine the relationship of those knowledge with their demographic characteristics. Methodology: To investigate nurse information relevant to Pneumothorax at Intensive Care Unit, a quantitative descriptive analysis used to assess approach with questionnaire items is performed. Throughout the non-probability sampling method, a purposive random sample of (30) nurses is chosen. A constructed questionnaire includes (socio-demographic data and knowledge questionnaire items), data was collection through the use of a questionnaire and self report nurses. Through the application the descriptive statistic, data were analyzed. Results: According to the analysis mean, the findings indicate that the majority (96.7 %) of nurses were poor knowledge. As well as, there were no significant relationship between nurses knowledge and their demographic characteristics at p-value more than 0.05. Conclusion: This research found knowledge in terms of Pneumothorax, nurses were poor knowledge. More years of experience in training the staff in intensive care unit and provide the health resources and exploiting young energies of nurses which indeed helps to develop their knowledge.